(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Because of the presence of a free carboxylic group, etodolac, a non-steroidal anti-inflammatory medication extensively used in arthritis, has been linked to stomach ulcers and irritation. The current study describes the production of an etodolac mutual amide prodrug by masking the free carboxylic group with glucosamine, a dietary supplement used to treat arthritis. The structure of the synthesised prodrug was confirmed and characterised using elemental and spectroscopic analyses, melting point, and migration parameters (Rf and RM) determined using thin layer chromatography and high-performance liquid chromatography, respectively. Prodrug in vitro reversion studies show a high incidence of colon pH reversal. Animals were used for in vivo pharmacological testing. In comparison to etodolac, the prodrug has good analgesic, anti-inflammatory, and anti-arthritic properties. Ulcerogeniticity analysis was used to examine the prodrug’s potential for harm. As a result, the prodrug has been shown to be more effective than etodolac and to have less gastrointestinal adverse effects.